Dietary patterns during high school and risk of colorectal adenoma in a cohort of middle‐aged women. Issue 10 (25th November 2013) - Nimptsch, Katharina; Malik, Vasanti S.; Fung, Teresa T.; Pischon, Tobias; Hu, Frank B.; Willett, Walter C.; Fuchs, Charles S.; Ogino, Shuji; Chan, Andrew T.; Giovannucci, Edward; Wu, Kana
<x xml:space="preserve">Abstract</x> Adolescent diet may be etiologically relevant for later risk of colorectal adenoma, a precursor of colorectal cancer. We aimed to examine associations between adolescent dietary patterns (derived using factor analysis) and risk of colorectal adenoma in middle adulthood. We analyzed data from 17, 221 women participating in the Nurses' Health Study II, who had completed a validated high school (HS) food frequency questionnaire in 1998 when they were 34–51 years old, and had subsequently undergone at least one lower bowel endoscopy. Between 1998 and 2007, 1, 299 women were diagnosed with at least one colorectal adenoma. In multivariable models adjusted for adult dietary patterns, a higher "prudent" pattern during HS, characterized by high consumption of vegetables, fruit and fish was associated with a statistically significantly lower risk of rectal (odds ratio [OR] highest vs. lowest quintile, 0.45, 95% CI 0.27–0.75, p‐trend = 0.005), but not colon adenomas. A higher "Western" pattern during HS, characterized by high consumption of desserts and sweets, snack foods and red and processed meat, was significantly associated with rectal (OR 1.78, 95% CI 1.12–2.85, p‐trend = 0.005) and advanced (OR 1.58, 95% CI 1.07–2.33, p‐trend = 0.08), but not associated with colon or non‐advanced adenomas. This study suggests that overall eating patterns during high school may influence later risk of rectal and advanced adenoma, independent of adult diet. Our results support the hypothesis that diet during early life may influence colorectal carcinogenesis.